Hebraiske ord i Jødernes hemmeligheder (1516) - Adams, Jonathan (Danske Studier, 2024)
In 1516, Poul Ræff printed Nouiter in lucem data: iudeorum secreta, his translation into Danish of Johannes Pfefferkorn’s vile anti-Jewish polemical Libellus de Judaica confessione (1508). The pamphlet aims to denigrate Judaism and Jews by ridiculing Jewish rituals, customs and beliefs; furthermore, it claims to reveal the Jews’ hidden secrets to its readers. These »secrets« include a number of words and phrases, best described as invectives, that the author says are used by the Jews when referring to Christians and aspects of their religion. These words are of particular philological and cultural-historiare to be found in print in a Danish work. In this article, I discuss how Hebrew phonology, morphology and syntax are realised in Nouiter in lucem data: iudeorum secreta, what the words mean, and how they can be placed into a context of Jewish-Christian polemic at the beginning of the modern era.